Clinical efficacy of daratumumab, pomalidomide, and dexamethasone in patients with relapsed or refractory myeloma: Utility of re‐treatment with daratumumab among refractory patients. Issue 17 (15th May 2019) - Nooka, Ajay K.; Joseph, Nisha S.; Kaufman, Jonathan L.; Heffner, Leonard T.; Gupta, Vikas A.; Gleason, Charise; Boise, Lawrence H.; Lonial, Sagar
Abstract : Background: The efficacy of daratumumab (DARA) both as a monotherapy and in combination with standard‐of‐care regimens in multiple myeloma (MM) has been established in clinical trials. This article presents a retrospective analysis of the safety and efficacy of DARA in combination with pomalidomide (POM) and dexamethasone (ie, daratumumab, pomalidomide, and dexamethasone [DARA‐POM‐D]) and, more importantly, the long‐term follow‐up of a cohort that was naive to DARA and POM as well as a cohort in which the utility of re‐treatment was evaluated among patients who were DARA‐ and/or POM‐refractory. Methods: Thirty‐four consecutive patients with relapsed and/or refractory MM treated with DARA‐POM‐D at the Winship Cancer Institute of Emory University from January 2015 through July 2016 were included in the analysis. The study was approved by Emory University's institutional review board. All received prior proteasome inhibitors and immunomodulatory drugs (IMiDs) and were refractory to their last line of therapy. Results: All patients were lenalidomide‐refractory, and 91% were bortezomib‐refractory. Two cohorts were identified on the basis of prior exposure to DARA and/or POM. Cohort 1 (12 patients) was DARA‐ and POM‐naive, and cohort 2 (22 patients) was DARA‐ and/or POM‐refractory. A subgroup of 12 patients in cohort 2 (cohort 3) was DARA‐ and POM‐refractory. The combination's tolerability was consistent with the results of the published phase 1b study (EQUULES) that evaluated the combination and no new safety signals were observed. The overall response rates (ORRs) were 91.7%, 40.9%, and 33.3% in cohorts 1, 2, and 3, respectively. Deep responses, including 4 stringent complete responses, were observed in cohort 1. In cohort 2, the ORR comprised 8 partial responses (PRs) and 1 very good PR. The median progression‐free survival (PFS) was not reached in cohort 1 at a median follow‐up of 41 months, and it was 3.2 months in cohort 2. DARA‐POM‐D not only was effective in DARA‐ and POM‐naive patients but also produced clinical responses in a third of patients re‐treated with these drugs. Conclusions: A better than quadrupled PFS benefit observed in cohort 1 in comparison with the previously reported benefit in the EQUULEUS trial (which led to US Food and Drug Administration approval of the DARA‐POM‐D combination) highlights the fact that the introduction of monoclonal antibody combination strategies and IMiDs as earlier lines of therapeutic options potentially could deliver better clinical outcomes. One‐third of patients refractory to separate lines of DARA and/or POM responded when they were re‐treated with a combination, and this resulted in survival benefits equivalent to those of other antimyeloma agents/combinations available for DARA‐refractory patients. Abstract : There are deep responses and no additional safety signals with daratumumab, pomalidomide, and dexamethasone in naive patients refractory to their last treatment. One third of patients who are refractory to separate lines of daratumumab and/or pomalidomide respond when they are re‐treated with a combination.